Mortality rate in hemodialysis patient in Edward Francis Small Teaching Hospital The Gambia - Yusupha Sanyang; Mamina Sambou (Elsevier, 2020)
Introduction: Mortality and admission rates are a reflection of the burden of diseases in a country and assessing the mortality pattern can also serve as an audit for the healthcare system. Aim: The study aimed to determine the mortality rate in hemodialysis patients at the Edward Francis Small Teaching hospital in the Gambia. Methods: The study was a retrospective cross-sectional study that reviews medical records to determine the mortality rate in hemodialysis patients in the hospital. 170 patients enrolled in the centre from 2016 to 2018 were included in the study. The records were reviewed and relevant sociodemographic such as the age and gender as well as causes of end-stage renal disease were collected. The mortality rate was calculated and the association between the variables and mortality was determined through chi-square test and binary logistic regression analysis. The ethical approval was sought from the research and ethical committee of the Edward Francis Small Teaching Hospital and the approval was given in January 2019. Results: The findings showed a high mortality rate among hemodialysis patients in the hospital, which was 84 (49.4%). A considerable amount of patients who underwent hemodialysis were females with a percentage of 57.6. The mean age of the patients was 43 years, ranging from 12 to 84 years. The three major conditions at the time of enrollment into the hemodialysis treatment were hypertension 42.9% and diabetes 15.5% with a significant number of patients diagnoses remaining unknown 28.6%. Significant relationship existed between gender and mortality, x2 (1, N = 149) = 6.985, P = 0.008. Females were more likely to be alive than the male OR 2.7 (1.33-5.19) P = 0.006. Conclusion: A higher mortality rate existed among maintenance haemodialysis patients in this facility. Therefore, more investment is needed in this centre to reduce the mortality rate.